2022
DOI: 10.1111/aje.13034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of end‐of‐century climate change on priority non‐timber forest product species across tropical Africa

Abstract: Plant species providing Non-Timber Forest Products (NTFP) are economically important across Africa. How this heterogeneous and understudied resource will respond to ongoing climate change remains understudied. Here, we modelled the impact of endof-the-century climate change on the distribution of 40 NTFP plant species distributed across tropical Africa. Occurrence data were extracted from a taxonomically verified database and three different ecological niche modelling algorithms were used. Species distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 84 publications
0
6
0
2
Order By: Relevance
“…Several studies have demonstrated the vulnerability of sub‐Sahara African tree species to climate change (De Cauwer et al, 2014; Blach‐Overgaard et al, 2015; Stévart et al, 2019; Dimobe et al, 2020; Jinga et al, 2020; Amoussou et al, 2022; Balima et al, 2022; Lyam et al, 2022; Ngarega et al, 2021). Mitigation measures have been proposed for the species imperilled by climate change, including establishment in protected areas that will remain climatically stable (Esser & Weldemariam, 2023; Warren et al, 2018) and introductions in future suitable habitats (Pimm et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have demonstrated the vulnerability of sub‐Sahara African tree species to climate change (De Cauwer et al, 2014; Blach‐Overgaard et al, 2015; Stévart et al, 2019; Dimobe et al, 2020; Jinga et al, 2020; Amoussou et al, 2022; Balima et al, 2022; Lyam et al, 2022; Ngarega et al, 2021). Mitigation measures have been proposed for the species imperilled by climate change, including establishment in protected areas that will remain climatically stable (Esser & Weldemariam, 2023; Warren et al, 2018) and introductions in future suitable habitats (Pimm et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several methods exist for selecting environmental variables to include in SDMs, each with advantages and disadvantages. Variables can simply be selected according to expert knowledge on how logically relevant they are to the species under study (Amoussou et al, 2022; Blach‐Overgaard et al, 2015). All variables can be used simultaneously and SDM algorithms are allowed to select the most important ones through variable permutation (Braunisch et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several methods are available to determine environmental variables to use in SDMs, each with advantages and disadvantages. Variables can be selected according to expert ecological knowledge on how relevant they are to the focal species (Amoussou et al., 2022 ; Blach‐Overgaard et al., 2015 ). Variables can be selected by permutation tests implemented in SDM algorithms, where those with high variable importance scores are selected (Braunisch et al., 2013 ).…”
Section: Methodsmentioning
confidence: 99%